Interacting with Compatriots in Russian Regions: the Experience of Tatarstan - R. R. Gimatdinov; I. R. Nasyrov (Vestnik MGIMO-Universiteta, 2015)
Work with compatriots promoting the cultural presence of Russia in the world becomes an important element of "soft power" Supporting the preservation and development among compatriots the cultural traditions of the Tatar people as components of ethnic and cultural diversity of Russia, Tatarstan participates in the implementation of the national foreign policy. The Republic of Tatarstan interacts constructively with the Russian Foreign Ministry, Rossotrudnichestvo, takes part in the activities of the Government Commission on Compatriots Abroad. Work with compatriots is carried out by the executive authorities of the republic within a number of regional government programs. The Coordination Council for the Affairs of Compatriots is created in Tatarstan .The sessions of the World Congress of Tatars (WCT) are held every five years. The Executive Committee of the WCT is in contact with one and a half hundreds of Tatar organizations in about 40 countries. The most important event in the in the cultural life of Tatar diaspora is celebration of Sabantui. The Days of the Republic of Tatarstan are also held abroad with great success,and they are aimed at strengthening bilateral cooperation together with the promotion of Tatar culture in the world.A special place in the activities of all the Tatar communities takes the honoring and support of the WWII and labor veterans. Work with the young people is the part of interaction with compatriots: youth forums and camps with the study of the Tatar language are organized. Attracting of compatriots to Tatarstan universities is carried out within Russian government programs.The work of strengthening business ties in the framework of the Tatar diaspora is conducted systematically. The interaction with various target groups of compatriots (women, scientists, cultural figures) is organized.The authors propose measures of uniting overseas communities of compatriots and exploiting their potential to promote the interests of the country and its regions.